Metabolic score for visceral fat is correlated with all-cause and cardiovascular mortality among individuals with non-alcoholic fatty liver disease - Chunming Xie; Xianpei Chen; Jiakun Zhang; Xueqing Jiang; Jing Xu; Hao Lin (BMC Gastroenterology, 2025)
Abstract Background Metabolic score for visceral fat (METS-VF) as an effective marker of visceral obesity has been correlated with non-alcoholic fatty liver disease (NAFLD). This study aims to explore the correlation between METS-VF and both all-cause mortality and cardiovascular disease (CVD)-related mortality among individuals with NAFLD. Methods A cohort of 6,759 subjects diagnosed with NAFLD was selected from the NHANES during the period from 1999 to 2018. Within this cohort, the prognostic utility of METS-VF for predicting CVD-related and all-cause mortality was assessed. Results There was a total of 1254 all-cause deaths (18.6%) and 418 CVD-related deaths (6.2%) at a median follow-up for 9.3 years. Multivariate Cox regression analysis and restricted cubic splines analysis indicated that METS-VF can exhibit a positive non-linearly correlation with CVD mortality (HR: 4.15, 95% CI: 2.31–7.44, p < 0.001) and all-cause mortality (HR: 5.27, 95% CI: 3.75–7.42, p < 0.001), with an identified inflection point at 7.436. Subgroup analyses further revealed a stronger correlation between METS-VF and all-cause mortality among subjects without diabetes. Furthermore, the areas under the curve (AUC) for 1-, 3-, 5-, and 10-year survival rates were 0.756, 0.740, 0.747 and 0.746 for all-cause mortality, and 0.774, 0.751, 0.746 and 0.758 for CVD mortality, respectively, which performs better than the other obesity and IR related index. Conclusion Elevated METS-VF independently contributes to an increased risk of both all-cause and CVD mortality in individuals with NAFLD. Clinical trial number Not applicable.